Summer of secrets [large type] : seasons of the heart - Hubbard, Charlotte, 1953- (Hubbard, Charlotte, 1953- Seasons of the heart., 2012)
"Summer has come to the cozy Amish town of Willow Ridge, but Rachael Lantz is looking forward to a whole new season in her life - marriage to carpenter Micah Brenneman, her childhood sweetheart. When a strange Englischer arrives in the Sweet Seasons Bakery Cafe claiming to be the long-lost sister of Rachel and her twin Rhoda, Rachel feels the sturdy foundation of her future crumbling - including Micah's steadfast love"--Page 2 of cover.